Tooth coloured restorative materials: recipe for a successful restoration - Harun, Nor Asilah (2015)
The success of a tooth coloured restoration depends on 3 main factors: the selection of a good quality materials, proper use of an appropriate bonding system and use of light curing system (if required) that is capable of delivering enough energy to properly complete the polymerization process. Consequently, any technical error committed during one of those three steps can resulted in clinical failure. The lecture will be discussing about factors and the accurate techniques for the restoration to be effective and have high survival rate.